THE ROLE OF PHARMACOGNOSY IN THE FORMATION OF A PHARMACIST - Sakhatska Іnna; Horoshko , Oleksandra; Zakharchuk , Oleksandr; Ezhned , Mariia; Matushchak , Marta; Kostyshyn , Liliia; Mykhailiuk , Nataliia (Collection of scientific papers «ΛΌГOΣ», 2022)
Introduction. Today, about 40% of drugs used for the treatment and prevention of diseases are herbal remedies [1]. Demand for herbal medicines is growing both in Ukraine and around the world. According to the World Health Organization, their share will be over 60% over a decade [2]. The pharmacist plays a key role in solving such topical issues as the search for plant sources and the creation of domestic effective medicines from natural raw materials, improving the quality of medicinal plant raw materials and herbal preparations, the rational use of natural resources. Therefore, the study of such a professional-oriented discipline as pharmacognosy plays an important role in the professional training of a highly competent specialist.